Food Supplements in Romania. Market, Controls, Compliance and Non-Compliance - Silvius STANCIU (Communications of International Proceedings, 2022)
Food supplements are products with an increasing frequency of consumption among Romanian consumers. Domestic legislation in the field of food production and marketing is correlated with European regulations. The official controls carried out periodically by the Romanian authorities with competences in the field have revealed a series of non-conformities, mainly related to improper labelling, storage or marketing. The deficiencies found can lead to serious damage to the health of the consumer, and measures are needed to reduce the risk factors. The analysis may be useful to the business community, consumers or food industry professionals to identify the best measures needed to protect the health and interests of consumers.
Keywords: food supplements; quality; controls; Romania